(untitled) (Research, Society and Development, 2020)
The scarcity of specific industrialized products for the pediatric public can impact the consumption of unlicensed drugs. Unlicensed drugs are those originating from licensed products, through modifications, in addition to imported ones, contraindicated ones and those that do not have information about the use in a certain group. This study aimed to investigate the prevalence of the use of unlicensed drugs, the drugs frequently prescribed in this context and the pharmaceutical forms of greatest production. In this sense, the methodology of integrative review of the scientific literature was used. The prevalence rates for the use of unlicensed medications ranged from 1.6 to 33.35%, demonstrating the diversity of the scenario according to the country studied. The drugs constantly prescribed were diuretics (furosemide, spironolactone and hydrochlorothiazide), folic acid, caffeine, phenobarbital and morphine. The pharmaceutical forms most frequently produced were liquid, with emphasis on solutions, suspensions and syrups. Although the pharmaceutical market has improved its productive capacity over time, the use of unlicensed drugs is still part of the pediatric care scenario in several countries.